THE EFFECTIVENESS OF USING ED SHEERAN SONG TOWARD STUDENTS’ PRONUNCIATION ABILITY - Nabil Chaniago; Amirudin Latif; Refai (Journal of English Education and Entrepreneurship (JEEP), 2025)
Pronunciation is very important for the students. Especially for beginners, most of the students have poor pronunciation ability. Their pronunciation ability still do not consistent and still far from correct with standard English pronunciation. In this research, the researcher applied Ed Sheeran song for learning pronunciation. Using English song is a great way to make the teaching and learning process becomes more attractive and fun. The purpose of this research was to know whether there were effect and significant difference between students who were taught by using Ed Sheeran song media and those who were not taught by using Ed Sheeran Song media toward students’ pronunciation ability at second grades SMP N 6 Metro in academic year 2024/2025. This research applied quasi experimental design. This research used two classes as experimental class and control class. The population was taken from the second grades students of SMP N 6 Metro in academic year 2024/2025. The numbers of the sample in this research were 30 students of class 8.8 as experimental class and 26 students of class 8.9 as control class. The results of the research showed that the Sig value (2-tailed) was 0.000 is lower than error level (0.05). According to the data analysis of the data and testing of hypothesis. The result of the calculation showed that the alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. Based on the computation above, it can be concluded that there are effect and significant difference using Ed Sheeran song in perfect as a media for leaning students’ pronunciation ability at the second grades of SMP N 6 Metro in academic year 2024/2025. In conclusion, the researcher concluded that English song can be used to relax students and provide an enjoyable classroom atmosphere and develop their motivation in learning pronunciation. In suggestion, for the future researcher can use song to improve the students understanding in language skills such as: Listening, Speaking, Reading and Writing. Song in this research is proved to be able to help students to reinforce what they learn in the classroom. But, learning English by using song takes an extra time in the regular meeting. It can be ineffective time for the learning process. As a matter of fact, every strategy or media bears some advantages and disadvantages. Therefore, it is important for the other researcher to consider each of advantages and disadvantages in order to make the implementation of the strategy in teaching process more effective and successful.